RANKINGS AND THEIR IMPACT ON A UNIVERSITY'S SCIENCE POLICY - van Dijk, P. Assoc. Prof. Jitse (Profese Online, 2013)
become increasingly important. The role of rankings regarding the current scientific policy of a university is explored. Several ranking systems currently exist: quantitative ones, some including aspects of quality or education, and web-based rankings. Dependent on their nature, different universities achieve a very different ranking. A university's strategic goal should be to have similar positions in different ranking systems, indicating that different fields at the university are equally developed. Universities that want to go the way of competing in research output with other universities in the world should facilitate their staff in regard to publishing in international journals.
Keywords: rankings; science policy